Evaluation of Cauda Epididymal Semen Quality of Crossbred Bulls in the Tropics - Vettical, Binoy S (International Journal of Applied Sciences and Biotechnology, 2016)
The objective of the study was to evaluate the quality of semen retrieved from cauda epididymis of crossbred bulls in the tropics. Testes from one hundred and twenty six recently slaughtered cross bred bulls in the tropics were used for the analyais. The total and progressive motility percentage obtained for epididymal semen were 49.17±9.26 per cent and 27.5±9.11 per cent respectively. The mean concentration obtained for epididymal semen was 37,175x106 ±7612x106 per ml. The mean percentage of live and dead sperms was 84.5±8.02 per cent and 15.5±8.02 per cent respectively. The mean percentage of normal spermatozoa, spermatozoa with abnormal heads, abnormal tails, spermatozoa with a proximal protoplasmic droplet and distal protoplasmic droplet were 35.67±2.30, 3.17±1.58, 2.33±0.61, 11.67±4.01 and 47.17±3.17 per cent respectively. Int J Appl Sci Biotechnol, Vol 4(1): 130-132